DEVELOPMENT OF FOOD SECURITY IN INDONESIA - Sujarwo Sujarwo; nuhfil hanani (Agricultural Socio-Economics Journal, 2016)
Agricultural policy in Indonesia has several steps historically. It is started from land distribution in old-order government of Sukarno. In that time, government focussed on distributing resources and preparing for agricultural development. However, lack of research and development of technology caused low in agricultural production and less food sufficiency. Bringing new perspective of agricultural development, new order government in 1960s brought significant progress in agricultural production in Indonesia but the farmers had to pay cost in depletion of agricultural resources and dependency in chemical fertilizer and pesticides in the production. Currently, more efforts are implemented in sustainable agriculture and diversification in food consumption expecting gains in getting higher nutrition status of individual, braking land conversion and increasing farmers’ income.